Disruption of the expression and function of microRNAs in lung cancer as a result of epigenetic changes - Watanabe, Kousuke; Takai, Daiya (Frontiers in Genetics, 2013)
Two decades have passed since the discovery of microRNA (miRNA), which determines cell fate in nematodes. About one decade ago, the conservation of miRNA in humans was also discovered. At present, the loss of certain miRNAs and the overexpression of miRNAs have been demonstrated in many types of diseases, especially cancer. A key miRNA in lung cancer was reported soon after the initial discovery of a tumor-suppressive miRNA in a hematological malignancy. Various causes of miRNA disruption are known, including deletions, mutations, and epigenetic suppression as well as coding genes. The recent accumulation of knowledge regarding epigenetic transcriptional suppression has revealed the suppression of several miRNAs in lung cancer in response to epigenetic changes, such as H3K9 methylation prior to DNA methylation and H3K27 methylation independent of DNA methylation. In this review, recent knowledge of miRNA disruption in lung cancer as a result of epigenetic changes is discussed. Additionally, emerging cancer-specific changes in RNA editing and their impact on miRNA function are described.